The scheme of shaping back surface of five-sided carbide inserts on CNC machines - E. V. Vasily’ev; Yu. A. Blokhina; M. M. Lakman (Омский научный вестник)
The methods of grinding the rear surfaces of multifaceted carbide inserts, as well as various schemes for shaping the back surfaces, are considered. The process of shaping the rear surface of a five-sided carbide insert is modeled. An algorithm for the implementation of the kinematic scheme for shaping the rear surface of pentahedral carbide plates using CAD tools has been developed. The processing of a multifaceted carbide inserts on a CNC grinding and grinding machine was carried out using the obtained mathematical dependence.